Structural, spectroscopic, and theoretical analysis of a molecular system based on 2-((2-(4-chlorophenylhydrazone)methyl)quinolone (2018)
A novel molecular system based on 2-((2-(4-chlorophenylhydrazone)methyl)quinoline (1-E) was synthesized. Interconversion of 1-E to its configurational isomer 1-Z was achieved using UV radiation (250 W Hg lamp). Such isomerization was monitored by 1H-NMR. The results suggest that the hydrazone derivative can act as a chemical brake in solution. This molecular system was structurally (Single Crystal X-Ray diffraction and DFT calculations) and spectroscopically (NMR, UV, and IR) characterized. Electrochemical measurements showed that configurational changes induce differential redox behavior. In this regard, the reported quinoline system exhibits different dynamic absorption and electrochemical properties that are modulated by the UV-light induced configurational change. Therefore, 1-E can be regarded as potential photo-electrochemical switch.